THE IMPACT OF TOXIC STRESS ON THE MORPHOFUNCTIONAL STATE OF THE HYPOTHALAMIC ARCUATE NUCLEUS IN THE CONDITIONS OF THE CHANGED MODE OF LIGHT EXPOSURE - S. V. Kotelnikova; A. V. Kotelnikov; V. F. Zaitsev (Юг России: экология, развитие)
Aim. Arcuate nucleus (AN) of the hypothalamus is one of the integrative centers responsible for energy metabolism in mammals. Reaction of the arcuatus nucleus of white rats on the toxic stress caused by introduction of cadmium chloride in the conditions of natural illumination, light and dark deprivations was studied.Methods. The toxicant was entered per os at a dose of 2 mg on 100 g of body weight a daily for 15 days after one month of adaptation to an the artificial photomode. Synthetic activity was estimated a method nucleoli volumes’ measurement on hematoxylin and eosin sections of the hypothalamus.Results. As light and dark deprivations led to the reduction of the nucleoli volumes of AN at animals of both sexes. Salt of cadmium in the conditions of natural illumination has caused reduction of the nucleoli sizes, but only in males. On the contrary, on the background of dark deprivation cadmium chloride led to decrease in activity of AN only in females. Light deprivation promoted increase in synthetic activity of AN neurocytes under the influence of cadmium salt in males, but did not change that in females.Conclusion. The impact of toxic stress induced by administration of cadmium chloride on the hypothalamic centre responsible for energy metabolism of the organism depends on light intensity and sex of the animal. Inhibition of the synthetic activity of AN by cadmium chloride in natural lighting is more pronounced in males, and in the dark of deprivation it is more pronounced in females.